Using the concept of film as a pen: An attempt to introduce the stamp of truth in the recording of the genocide of Yazidi women in 2014 - رحیم, أ .م . د.دڵشاد مستەفا رحیم (Sulaimani Journal for Humanities, 2024)
In the 1950s, French cinema critic Alexander Astrac introduced a new concept that became the manifesto of the new wave of French cinema and spread around the world as a concept. The concept of the camera/pen, in which Astrak introduced cinema as language, just as literature has its own language (this assumption, of course, later led to many arguments). In this context, the director treats the camera as the main factor of production just as the writer treats the pen. That is, the camera can express all the things that are hidden inside people, and in the case of writing, the pen takes on this task. In this situation, cinema goes beyond being a source of joy and becomes a means of expression, allowing us to convey what other languages and tools may not be able to convey. It is somewhat different from the secrecy and silence of stories and events. If we repeat the experience of this act with these cases and situations, creating an environment where the victim trusts the camera as a medium to record what they cannot tell openly to others, we may reach a situation that brings comfort and breaks the terrible silence created by social and traditional oppression. This study attempts to find a code of relationship between the concept of the camera and the situation of Yazidi women in trusting and treating the camera as a pen to record a painful and foggy memory. It is a step to invite different terms and concepts into the field of finding cinematic forms for the tragedies and miseries that have befallen the Kurds. In this attempt, the situation of Yazidi women is targeted
Keywords: Language of Cinema; Genocide; Silent and Silent; Victim Memory